Opportunities for increasing labor efficiency based on human capi- tal management - VASILIEVA, ANASTASIA V. (The journal of contemporary issues in business and government, 2020)
An approach is proposed that makes it possible to increase the efficiency of labor at the level of the type of economic activity through the management of the human capital of organiza- tions. Based on the analysis of the rating of the human development index, the most important gaps in the key parameters of the rating were identified and the priority directions for increasing the level of the human development index were substantiated. The structure of the system for managing the formation of human capital within the framework of the type of economic activity was formed, on the basis of which a hierarchy of tasks for managing human capital was developed in the scale of the type of economic activity based on the Ishikawa diagram. The author’s algorithm for assessing the influence of factors of the external and internal environment on the state of human capital in the scale of the type of economic activity has been built, and the key factors of motivating intellectual workers to continue working in this organization have been identified.